Effect of electroacupuncture to prevent selenite-induced cataract in Wistar rats - Cariello,Angelino Julio (2006)
PURPOSE: To investigate whether electroacupuncture can prevent selenite-induced cataract in an experimental model. METHODS: Fifty Wistar rat pups were randomized into 5 groups of 10 animals: Group 1 (control), no procedure was performed; Group 2 (selenite), sodium selenite (30 micromoles/kg body weight) was injected subcutaneously between postpartum days 10 to 12; Group 3 (anesthesia) received the same dose of selenite and underwent ether inhalation anesthesia during 10 minutes daily for one week; Group 4 (electroacupuncture) underwent the same procedure of Group 3, but also receiving electroacupuncture (2 Hz, 50 mA) applied to the Neiguan (PC6) and Guangming (GB37) acupoints during the anesthesia period; and Group 5 (Sham) underwent the same procedures of Group 4, but needles were applied to non-acupoints. The development of cataract was assessed one week later, and its density was graded by slit lamp biomicroscopy. RESULTS: All control rats lenses (Group 1) were clear. Groups 2, 3 and 5 rats developed more severe cataract or complete opacification. In Group 4 (electroacupuncture), 45% of eyes did not develop cataract while thirty per cent developed less severe cataract than Groups 2, 3 and 5. The between-group difference was statistically significant (p<0.001). Lens opacification grade in Groups 1 and 4 was lower than in the Groups 2, 3 and 5 (p<0.001). CONCLUSION: Electroacupuncture effectively decreased selenite-induced cataract formation rate in pup rats when needles were applied at specific acupoints.